Can a Use-based Taxonomy be Natural? An example from Aguaruna folk classification of trees - Jernigan, Kevin (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> <![endif]–> This work examines the classic utilitarian vs. intellectualist debate in cognitive ethnobiology from a new perspective. It challenges the notion that classifications based on utility are artificial, that is, necessarily constructed from a few special characteristics. The paper involves a new analysis of ethnographic data collected by the author over multiple field sessions from 2004 to 2010 in nine Aguaruna villages in Amazonas, Peru. In previous work, Aguaruna participants described uses, along with sensory and ecological characteristics of local tree species. They also stated which tree folk genera they consider related to each other as “companions,” typically placing taxa together in natural groupings. This new synthesis took the descriptions of uses and physical characteristics for a sample of 41 Aguaruna tree folk genera and subjected both to hierarchical cluster analysis to see which would better reproduce the folk classification. Use data performed nearly as well as sensory data in reproducing the natural groupings of trees. This makes sense considering that plant uses tend to be based on physical properties (including presence of secondary compounds) that related species will often share. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>